Development of 'My Meal Mate' – A smartphone intervention for weight loss. Issue 1 (7th February 2013) - Carter, M. C.; Burley, V. J.; Cade, J. E.
Summary Obesity is a major public health issue and research is turning to information communication technologies as a means to deliver weight management interventions. A smartphone application (app) which allows the user to self monitor food intake and physical activity could be one such convenient and wide reaching approach. A smartphone app called 'My Meal Mate' (MMM) has been developed which uses behavioural strategies of goal setting, self monitoring and feedback to aid weight management. The development of the app has been informed by focus groups with potential system users and by benchmarking against popular diet tracking applications available to download. This paper describes the MMM app, discusses its development and outlines plans for further investigation.